Pengaruh Sari Buah Naga Merah (Hylocereus polyrhizus) Terhadap Daya Tahan Hidup Spermatozoa Babi - Seran, Sherlina Victoria; Foeh, Nancy D. F. K.; Ndaong, Nemay A. (JURNAL KAJIAN VETERINER, 2023)
The aim of study was to determine the effect of the red dragon fruit juice (Hylocereus polyrhizus) on the viability of boar spermatozoa. The semen was contained from a healthy two year old male, using dummy sow's help. Good quality cement is divided into 5 groups where red dragon juice is added; 100 L (P1); 200 L (P2); 300 L (P3); 400 L (P4); 500 L (P5) deep in natural dilution and stored at prescribed temperatures. Spermatozoa's life observations were performed daily for every two hours of observation. A descriptive analysis of macroscopic and microscopic semen is obtained. The liquid semen evaluation data is analyzed using Analysis Of Variance (ANOVA). If there is a real difference in treatment, then a follow up test with Duncan to compare the results to each treatment. This study indicates that the real addition of coconut water thinkers and antioxidants of red dragon fruit (P<0,05) to the durability of boar spermatozoa. Treatment by applying the 200µL/mL of red dragon fruit (Hylocereus polyrhizus) to the treatment of the rhizus fruit (Hylocereus polyrhizus) to the treatment of the semen was effective in sustaining the viability of spermatozoa was shown by its 50,96% motility value with a 20 hour deposit.